2014
DOI: 10.1136/archdischild-2013-305748
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic challenges of primary autoimmune haemolytic anaemia in children

Abstract: Autoimmune haemolytic anaemias (AIHAs) are extracorpuscular haemolytic anaemias produced by antierythrocyte autoantibodies which cause a shortened red blood cell life span. There are several reasons why the diagnosis and treatment of AIHAs in children represent a bigger challenge than in adult patients, including the presence of particular AIHA types, the uncertainty of serological tests and the limited clinical experience. All these facts have added up to a poor understanding and management of some topics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
0
18
1
2
Order By: Relevance
“…We report a similar median age for cats with primary IMHA in this study (4.2 years), and also show that cats within the age range from 2.1 to 5.9 years were significantly more likely to develop primary IMHA than any other age group. This age of onset differs from those reported in dogs and people, in whom the diagnosis is made more frequently in middle or older age groups …”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…We report a similar median age for cats with primary IMHA in this study (4.2 years), and also show that cats within the age range from 2.1 to 5.9 years were significantly more likely to develop primary IMHA than any other age group. This age of onset differs from those reported in dogs and people, in whom the diagnosis is made more frequently in middle or older age groups …”
Section: Discussioncontrasting
confidence: 85%
“…This age of onset differs from those reported in dogs and people, in whom the diagnosis is made more frequently in middle or older age groups. [23][24][25] Siamese cats appeared to be overrepresented among the cases with primary IMHA, but this association did not reach significance and the odds ratio had a large CI because of the small number of Siamese cats with IMHA. We cannot therefore conclude that any particular breed is predisposed to development of primary IMHA, but the results of our investigation are in agreement with previous studies that showed that the majority of cases were diagnosed in genetically outbred (domestic short-haired) cats.…”
Section: Discussionmentioning
confidence: 92%
“…However, also other infectious culprits have been implicated (eg, EBV, HIV, ParvoB19, HHV6, HCV, helicobacter pylori, and mycoplasma pneumoniae) . Cold antibodies are reported in circa 10%‐30% of cases of AIHA after SOT . The presence of the donor spleen and the use of tacrolimus has also been suggested to be risk factors for AIC after SOT in some papers, but disputed by others .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the donor spleen and the use of tacrolimus has also been suggested to be risk factors for AIC after SOT in some papers, but disputed by others . One important factor, which has to be excluded, is the presence of PTLD (associated with 8% of cases with AIC) or other underlying malignancy or autoimmune disease …”
Section: Discussionmentioning
confidence: 99%
“…This disease involves the binding of autoantibodies, either IgG and/or IgM, to the red blood cell (RBC) surface antigens resulting in their destruction via the reticuloendothelial system or the complement system . For the majority of AIHA cases, regardless of etiology, corticosteroids are first‐line therapy . This point is evidenced by one of the largest contemporary single‐institutional series of AIHA in children where 100% of the patients received steroids as first‐line treatment .…”
Section: Introductionmentioning
confidence: 99%